Odpowiedzi

2010-03-11T18:33:55+01:00
A)x=5-2/3
x=4,1/3
b)0,5x-3+1=0,75x+4,5-5
0,5x-0,75x=4,5-5+3-1
-0,25x=1,5 /*(-4)
x=(-6)
c)1,5y+3+2y=5y+2,5-5
1,5y+2y-5y=2,5-5-3
(-1,5y)=(-0,5) /-1,5
y=1/3




Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-11T18:33:55+01:00
A) x -2/3=5
x=5 +2/3
x=15/3+2/3
x=17/3
x=5i2/3
b)1/2(x+6)+1=3/4(x+6)-5
1/2x+3+1=3/4x=4,5-5
1/2x-3/4x=4,5-5-3-1
-0,25x=-4,5
x=18
c)1,5(y+2)+2y=5/2(2y+1)-5
1,5y+3+2y=5y+2,5-5
1,5y+2y-5y=2,5-5-3
-1,5y=-5,5
y=5,5/1,5
y=55/15
y=3i10/15
y=3i2/3
2010-03-11T18:35:21+01:00
A.) x-2/3=5 | *3
x-2 = 15 | +2
x = 17

b.) 1/2(x-6) + 1 = 3/4 (x+6) - 5


c.) 1,5 (y + 2) + 2y = 5/2 (2y + 1) - 5